Delayed diagnosis of a primary intraosseous squamous cell carcinoma: A case report - Abdelkarim, Ahmed Z. (Imaging Sci Dent, 2019)
Primary intraosseous squamous cell carcinoma is a rare malignant central jaw tumor derived from odontogenic epithelial remnants. Predominantly, it affects mandible, although both jaw bones may be involved. This report describes a 60-year-old man who was initially misdiagnosed with a periapical infection related to the right lower wisdom tooth. After four months, the patient presented to a private dental clinic with a massive swelling at the right side of the mandible. Panoramic radiographs and advanced imaging revealed a lesion with complete erosion of the right ramus, which extended to the orbital floor. A biopsy from the mandibular angle revealed large pleomorphic atypical squamous cells, which is the primary microscopic feature of a poorly differentiated squamous cell carcinoma.